Healthcare inequities and healthcare providers: we are part of the problem - Crystal N. Campbell (International Journal for Equity in Health)
Abstract Background The United States (U.S.) spends the highest amount on healthcare globally, at $12,434 per capita, yet experiences poor health outcomes, including lower life expectancy and higher rates of preventable mortality. With a life expectancy of 76.4 years, the U.S. lags behind other high-income countries, which have an average of 81.1 years. Health inequities, especially among marginalized racial and ethnic groups, contribute significantly to these disparities. Implicit bias among healthcare providers plays a critical role in perpetuating these inequities, resulting in misdiagnoses, undertreatment, and patient mistrust. Purpose This paper examines the role of implicit bias in healthcare disparities, its impact on marginalized populations, and the ethical responsibility of healthcare providers in mitigating bias. It explores the neuroscientific and psychosocial mechanisms of implicit bias and its effects on patient outcomes. Methods A literature review was conducted using PubMed, APA PsycNet, JSTOR, ProQuest, and Google Scholar. The search included peer-reviewed articles from 2008 to 2025 discussing implicit bias in healthcare, its effects on marginalized groups, and evidence-based mitigation strategies. Exclusion criteria included responses and commentaries. Findings Quantitative findings on implicit bias mitigation strategies show mixed results. Counter-stereotypic strategies and intention-setting interventions reduced Implicit Association Test (IAT) scores by 0.15 at 4 weeks and 0.17 at 8 weeks. However, some strategies, like stereotype replacement and intergroup contact, consistently showed measurable positive effects. Qualitative findings revealed that simulation-based training and perspective-taking significantly increased self-awareness, empathy, and behavioral changes in healthcare providers. Mindfulness meditation and emotional regulation techniques helped reduce stress and bias in high-pressure settings. These findings suggest that while some strategies are effective in the short term, long-term success requires ongoing training, continuous reflection, and practical application in clinical practice. Conclusion Health inequities in the U.S. are a public health crisis, disproportionately affecting marginalized groups. These disparities are preventable, yet persistent due to systemic issues. Healthcare providers must address implicit biases and commit to unbiased, ethical care. Institutions must prioritize health equity through inclusive cultures, comprehensive bias training, and accountability, exemplified by efforts like UW Medicine’s bias incident reporting.